Impact of Information Sharing and Quality Assurance on Customer Service in Nepalese Commercial Banks - Chawal, Cristina; Mandal, Babbi; Pandey, Bibek Raj; Regmi, Degendra; Ram, Devendra Kumar (Nepalese Journal of Economics, 2025)
This study examines the impact of information sharing and quality assurance on customer service in Nepalese commercial banks. Customer service is the selected dependent variable. The selected independent variables are information sharing, quality assurance, privacy concern, technology utilization, staff training and communication. The study is based on primary data with 106 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of information sharing and quality assurance on customer service in Nepalese commercial banks. The study showed that information has positive effect on customer service. It indicates that better information sharing to the customer leads to increase in customer service. Likewise, quality assurance has positive effect on customer service. It indicates that higher quality assurance leads to increase in the level of customer service in Nepalese commercial banks. Moreover, technology utilization has positive effect on customer service. It implies that more technology utilization leads to increase in the level of customer service in Nepalese commercial banks. Similarly, privacy concern has positive effect on customer service. It implies that higher concerned towards security and privacy leads to increase in customer service. Likewise, staff training has positive effect on customer service. It states that increase in staff training leads to increase in customer service in Nepalese commercial banks. Similarly, communication has positive effect on customer service. It shows that better communication with the customers leads to increase in customer service.